Pengaruh good corporate governance dan corporate social responsibility terhadap kinerja keuangan dengan manajemen laba sebagai variabel mediasi pada perusahaan manufaktur tahun 2019-2023 - Musthafa Kemal Zasha (Jurnal Ilmu Manajemen, 2025)
This study aims to examine the variables that may influence the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The independent variables used in this research include the proportion of independent commissioners, institutional ownership, audit quality, and corporate social responsibility (CSR). Earnings management is employed as a mediating variable to determine whether it can mediate the relationship between the independent variables and the dependent variable, financial performance. This research applies a purposive sampling method, with a total sample of 15 manufacturing companies. The data analysis technique employed is panel data regression, which was processed using STATA 17 software. The results indicate that the proportion of independent commissioners, institutional ownership, audit quality, and CSR do not have a significant effect on financial performance. Furthermore, earnings management is also unable to mediate the relationship between those independent variables and financial performance. These findings provide implications for management and investors in understanding the factors that influence a company’s financial performance.